Demotivational meaning of words in the Armenian language - Felekyan, Manuk (Bulletin of Yerevan University B: Philology, 2025)
During the historical development of a language, the semantic structure of a compound word can change, which can lead to a blurring of the word's complex structure, even to its loss. This phenomenon is called demotivation.The formation of the meaning of a compound word is based on its internal form and its motivation. The internal form of a compound word can be very clear and easily understood by native speakers of a given language. This is true for the vast majority of compound words. However, under certain conditions, language tends to obscure and lose both the word-formation and semantic connections within a compound word. Sometimes, the internal form is virtually lost, resulting in a loss of understanding of the compound nature of the word.This article examines the main reasons and stages of demotivation of the meaning of words in the Armenian language.
Keywords: internal form of the word; external form of the word; semantic motivation; structural motivation; motivating feature; demotivation; semantic shifts of vocabulary; simplification and redefinition